“Please forward before they delete it!” Assessing conspiracy theories and disinformation in chain e-mails about Covid-19 in the Czech Republic [version 1; peer review: 2 approved, 2 approved with reservations] - Ondrej Filipec (Routledge Open Research)
The outbreak of the pandemic, marked with many unknowns and uncertainty, provided a fertile ground for disinformation, conspiracy theories, and pro-Kremlin propaganda in the Czech Republic which was delivered through various communication channels. This is also the case of so-called “chain e-mails” forwarded especially among older people to substitute social networks. The main aim of the article is to reveal the nature and content of chain e-mails communicating Covid-19 with a special focus on narratives and its development. The article is based on the analysis of 2,056 unique Covid-19-related chain e-mails forwarded among people in the Czech Republic between March 2020 and May 2022. Next to revealing key targets, techniques, and narrative developments, the analysis contributes to a better understanding of disinformation, propaganda, and conspiracy theories in the Czech Republic and the (dis)information ecosystem in general. The final discussion is dedicated to the possibilities of how to address the negative effects of chain e-mails.